MODEL PENGUATAN MATERI FIKIH DENGAN KONSEP SYARAT KECAKAPAN IBADAH AMALIAH (SKIA) DI MI AL AZHAR SENDURO LUMAJANG - Mahmuda, Imaniar; Hafid (Qolamuna : Jurnal Studi Islam, 2026)
This research  is based on the need to improve students' understanding and skills in performing worship in accordance with Islamic jurisprudence  (fiqh) guidance in a practical and applicable way. This study aims  to  examine  a  model  for  reinforcing  Islamic  jurisprudence  material  based  on  the concept  of the requirements  for practical  worship  skills  (SKIA)  and  to assess  its  effectiveness  in  improving  students' overall  ability  to practice  worship.  The research  method  used  was  a  descriptive  qualitative  approach. Data  collection  techniques  were  conducted  through  observation,  interviews,  and  documentation.  The results indicate that the application  of the SKIA model can improve students' conceptual understanding and  practical  skills  in  worship,  such  as  ablution,  prayer,  an d  fasting.  This  model  emphasizes  the integration  of  understanding  of Islamic  jurisprudence  theory  and  the practice  of worship,  taking  into account  the  requirements  of  students'  age, mental  ability,  and  knowledge.  Thus,  the SKIA  model  has proven  effective in strengthening Islamic jurisprudence  learning in a more contextual  way and oriented towards developing students' religious competence.. Keywords: Fiqh, Material Reinforcement, Model SKIA.